Golden Balls and Moon Forehead : Understanding Ancient Korean Performing Arts through the Japanese Court Dances - SUH, Johng-Rook (THE HALLYM JOURNAL OF JAPANESE STUDIES, 2017)
This study is a research to understand the ancient Korean dances through the analysis of Five poems regarding various Korean performances(鄕樂雜詠五首Hyangak chapyŏng osu) particularly, ‘Kŭmhwan’ (金丸) and ‘Wŏlchŏn’ (月顚). With the study, we may find Kŭmhwan is a juggling dance to wish to make peace. We could also discover that the poet watched this performance in Ulsan area or Kyŏngju. In addition, Tamatori (弄玉) in an old Japanese painting could be related to Silla Kŭmhwan. On the other hand, Wŏlchŏn could be connected to the Wine-drinking Game in the Ancient East Asia. It is interesting that The Japanese court dance Kotokuraku (胡德樂) is quite similar to Wŏlchŏn. Through the comparison between Wŏlchŏn and Kotokuraku, we could explain why the mask of Kotokuraku has a wrenched nose. Korean idiomatic phrase has a similar expression to the Kotokuraku mask: “as crooked as the nose (코가 삐뚤어질 만큼)”. It corresponds well with the theme of Kotokuraku. Through the comparison, we could also guess that the meaning of the unique title Wŏlchŏn may depict the nose of the mask. In this sense, we can assume that the mood of this dance could be funny and comical. KCI Citation Count: 1